2010
DOI: 10.1590/s0103-50532010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of azo dye acid black 1 under the suppression effect by chloride ion

Abstract: O objetivo deste estudo é determinar a cinética degradação do corante Acid Black 1 por ação oxidante do ozônio e avaliar a influência da contaminação de íons cloreto na degradação deste corante. Foram observadas cinéticas de pseudo-primeira ordem, tanto para a degradação das estruturas cromóforas (620 nm), quanto das aromáticas (321 nm). A completa remoção da coloração foi verificada em 25 min ([corante] 0 = 1,8 × 10 -5 mol L -1 ), enquanto que as estruturas aromáticas foram degradadas com menor velocidade. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…It was further found that distinct peaks appeared in the UV spectrum after the application of APs (Figure b). It is known that antibacterial reactive chlorine species, for example, hypochlorite can be electrochemically generated and that they may have distinct UV signals. It was recognized that the UV absorption signals of hypochlorite change upon protonation. We confirmed this mechanism by recording the UV–vis spectrum of hypochlorite in artificial seawater at low (pH ≈ 2.6) and high pH (pH = 8.1), see Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…It was further found that distinct peaks appeared in the UV spectrum after the application of APs (Figure b). It is known that antibacterial reactive chlorine species, for example, hypochlorite can be electrochemically generated and that they may have distinct UV signals. It was recognized that the UV absorption signals of hypochlorite change upon protonation. We confirmed this mechanism by recording the UV–vis spectrum of hypochlorite in artificial seawater at low (pH ≈ 2.6) and high pH (pH = 8.1), see Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…Decolourization efficiency was 94% after 25 min of ozonation investigated in this study. Ozonation treatment leads to a complete decolourization of the Acid Black 1 dye solution in 25 min (Paprocki, Dos Santos, Hammerschitt, Pires, & Azevedo, 2010). A rapid decline in color (Pt-Co scale) and absorbance shows that the decolouration dynamics in Figure 5.…”
Section: Effect Of Ozonation On Dye Wastewatermentioning
confidence: 95%
“…Concentration of nitrate formed during reaction was monitored ( Figure 6) and results showed much formation of nitrate ions is obtained at pH 3 (4.15 mg/L). The remaining nitrogen atoms could be in nitro form or may be converted to nitro-intermediates that more resistant to ozone attack 21 .…”
Section: Ozonation Of 4ncbmentioning
confidence: 99%